Effective vocational guidance as a protective factor in the development of vocational distress (2020)
Stress as a psychopathological syndrome shows a prevalence between 1 % and 2 % of the world population. The normal conditions of daily life can become a threatening agent when the individual does not have the psychological and physical resources to respond to the situation. Vocational distress is the response of tension and discomfort to the stimuli and demands derived from vocational development. This includes vocational decision, loss of employment, perception of self-efficacy, tensions between study-family-work, among others. In this research article, the narrative review research documentary methodology was used; obtaining as result the relevance of effective vocational guidance is related as a preventive strategy to the possibility of developing vocational distress. Achieving that the process of vocational guidance becomes the context where the individual is provided with a repertoire of cognitive-behavioral tools essential for decision-making, resilience, self-esteem, self-efficacy, and vocational maturity, which are established as factors of protection against the risk of mental and psychophysiological diseases. This writing contributes to the prevention of mental disorder of possible appearance in the dimensions of study and work, understanding their benefits to the mitigation of risk factors, according to the recommendations of the World Health Organization.Key words: Vocational orientation, vocational distress, vocational stress, stress, distress, protective factors, risk factors, education, educational psychology.